Issue of the preservation of Zakhchin folk songs - V. Yanjindulam; B. Altantuya; S. Ayanur (Nomadic Civilization: Historical Research, 2025)
In this article, the authors analyze folk songs. The authors have recorded more than 80 songs in the Altay soum of the Kobdo aimag from 79-year-old Parz Tsagaana Myadag. The Zakhchin people live in this soum. Some of the songs are performed during the wedding ceremony. The wedding ceremony begins with the song “Zhargalt kheer mor”. The song “Unagan bietey ulaan” is performed when the bride is taken out of her parents’ house and the remaining guests sing “Ermen zhoroo bor”/ when the bride is taken to the groom’s house they sing the song “Golyn tsagaan burgas”, then they say good wishes to the bride’s mother and the groom’s side presents her with a gift, and also sing the song “Tsagaanaa tsohor mor”. The wedding ceremony ends with the song “Bichgen kheer mor”. The songs of Ts. Myadag preserved the dialectal features of the Zakhchin people. The authors of this article propose to continue collecting and publishing songs, replicating them on CDs, and also including them in the secondary school curriculum as a subject of regional competence in order to preserve the traditions of the folk song